Modulation of charge carrier mobility by side-chain engineering of bi(thienylenevinylene)thiophene containing PPE-PPVs - Jadhav, Rupali R.; Camaioni, Nadia; Oppelt, Kerstin; Tinti, Francesca; Gazzano, Massimo; Fattori, Valeria; Wadgaonkar, Prakash P.; Rathgeber, Silke; Hoppe, Harald; Egbe, Daniel A. M. (RSC Advances, 2016)
Four 2-dimensional conjugated poly(p-phenylene-ethynylene)-alt-poly(p-phenylene-vinylene) polymers containing a lateral bi(thienylenevinylene)thiophene unit (BTE-PVs) were synthesised and characterised. The investigated polymers share the same conjugated structure, but differ in the anchoring positions of solubilising linear octyloxy/branched 2-ethylhexyloxy side-chains. UV-vis spectra of the polymers in dilute chloroform solutions and as thin films were studied. X-Ray diffraction patterns as well as the bulk charge transport of polymer films cast from chlorobenzene solutions were also investigated. A dramatic effect of the solubilising side-chains on the charge carrier mobility of BTE-PV films was observed, with bulk hole mobility values ranging between 1.3 x 10(-5) cm(2) V-1 s(-1) and 2.2 x 10(-2) cm(2) V-1 s(-1), which is not ascribable to evident structural variations of the polymer films. It is shown that the combination of linear octyloxy and branched 2-ethylhexyloxy side-chains is favorable for the charge transport properties of BTE-PVs, compared to the incorporation of only linear or only branched side-chains.

Crystallisation-enhanced bulk hole mobility in phenothiazine-based organic semiconductors - Shinde, D. B.; Salunke, Jagadish K.; Candeias, Nuno R.; Tinti, Francesca; Gazzano, Massimo; Wadgaonkar, P. P.; Priimagi, Arri; Camaioni, Nadia; Vivo, Paola (Scientific Reports, 2017)
A series of three novel donor-acceptor systems based on C(3)-malononitrile-substituted phenothiazines was synthesised in good overall yields and their thermal, spectroscopic, and electrochemical properties were characterised. The compounds were prepared through a sequence of Ullmann-coupling, Vilsmeier-Haack formylation and Knoevenagel-condensation, followed by Suzuki-coupling reactions for introduction of aryl substitutents at C(7) position of the phenothiazine. The introduction of a donor unit at the C(7) position exhibited a weak impact on the optical and electrochemical characteristics of the compounds and led to amorphous films with bulk hole mobilities in the typical range reported for phenothiazines, despite the higher charge delocalisation as attested by computational studies. In contrast, highly ordered films were formed when using the C(7)-unsubstituted 3-malononitrile phenothiazine, exhibiting an outstanding mobility of 1 x 10(-3) cm(2) V-1 s(-1), the highest reported for this class of compounds. Computational conformational analysis of the new phenothizanes suggested that free rotation of the substitutents at the C(7) position suppresses the ordering of the system, thereby hampering suitable packing of the new materials needed for high charge carrier mobility.